1998
DOI: 10.1016/s0014-5793(98)01259-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular anatomy of the human glucose 6‐phosphate dehydrogenase core promoter

Abstract: The gene encoding glucose 6-phosphate dehydrogenase (G6PD), which plays a pivotal role in cell defense against oxidative stress, is ubiquitously expressed at widely different levels in various tissues; moreover, G6PD expression is regulated by a number of stimuli. In this study we have analyzed the molecular anatomy of the G6PD core promoter. Our results indicate that the G6PD promoter is more complex than previously assumed; G6PD expression is under the control of several elements that are all required for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
(28 reference statements)
1
25
0
Order By: Relevance
“…The positioning extends into the transcriptional unit, about 1 kb beyond the limits of the CpG island. This may suggest that this region contributes to the chromatin organization of the G6PD gene in human cells and to the control of its expression (12).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The positioning extends into the transcriptional unit, about 1 kb beyond the limits of the CpG island. This may suggest that this region contributes to the chromatin organization of the G6PD gene in human cells and to the control of its expression (12).…”
Section: Resultsmentioning
confidence: 96%
“…It carries the 3Ј part of the gene coding for G6PD including the first two exons as well as the accompanying CpG island. A DNA segment extracted from the island (nucleotide 2528 -2654 from the beginning of the insert) was capable of acting as a core promoter, assuring the regulation of expression of a reporter gene in mammalian but not in Drosophila cells (12). The full nucleotide genomic sequence of the region is available from GenBank™ (Locus HUMFLNG6PD).…”
Section: Methodsmentioning
confidence: 99%
“…Of these, Motifs 3 and 4 had been shown previously to be part of the essential core promoter 24 and had been validated as bona fide Sp1 binding sites in vitro. 25 To dissect the role of cis DNA elements in G6PD transcription, we first carried out a promoter deletion analysis. In both the absence and the presence of NaBu, G6PD promoter activity depended on a proximal 562-bp promoter fragment containing 7 GC-rich motifs, Figure 1.…”
Section: Sp1-dependent Increase In G6pd Transcription In Response To mentioning
confidence: 99%
“…Enhanced activity of G6PDH, a lipogenic enzyme, was found at diabetes and obesity (Gupte, 2010). In humans, G6PDH is regulated by many transcription factors, in particular, SREBP-1a (sterol regulatory element binding protein) (Amemiya-Kudo et al, 2002), AP-1 (Kletzien et al, 1994) and Sp1 (Franzè et al, 1998). It was shown that elevation of G6PDH activity might lead to enhanced lipid synthesis (Salati et al, 2001;Park et al, 2005;Lee et al, 2011) and to possible reductive stress (Dimmeler & Zeiher, 2007;Rajasekaran et al, 2007;Ralser & Benjamin, 2008).…”
Section: Wwwintechopencommentioning
confidence: 99%